2011
DOI: 10.1016/j.chemgeo.2011.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Rapid oxidation of mercury (Hg) at volcanic vents: Insights from high temperature thermodynamic models of Mt Etna's emissions

Abstract: A major uncertainty regarding the environmental impacts of volcanic Hg is the extent to which Hg is deposited locally or transported globally. An important control on dispersion and deposition is the oxidation state of Hg compounds: Hg(0) is an inert, insoluble gas, while Hg(II) occurs as reactive gases or in particles, which deposit rapidly and proximally, near the volcanic vent. Using a new high temperature thermodynamic model, we show that although Hg in Etna's magmatic gases is almost entirely Hg(0) (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 67 publications
0
13
1
Order By: Relevance
“…In our samples, Hg was detected in concentrations of~1 ppb, which were~2.5-3.5 orders of magnitude lower than measurements on other volcanoes (Olmez et al, 1986;Symonds and Reed, 1993;Taran et al, 1995;Nriagu and Becker, 2003;Bagnato et al, 2007;Witt et al, 2008;Martin et al, 2011;Mather et al, 2012).…”
Section: Concentrations Of Trace Elements In Erta Ale Gasescontrasting
confidence: 69%
“…In our samples, Hg was detected in concentrations of~1 ppb, which were~2.5-3.5 orders of magnitude lower than measurements on other volcanoes (Olmez et al, 1986;Symonds and Reed, 1993;Taran et al, 1995;Nriagu and Becker, 2003;Bagnato et al, 2007;Witt et al, 2008;Martin et al, 2011;Mather et al, 2012).…”
Section: Concentrations Of Trace Elements In Erta Ale Gasescontrasting
confidence: 69%
“…Trace elements released from the magma as vapors generally condense at the vent enabling the total emission of trace elements to be assessed through particle measurements alone [e.g., Symonds and Reed , 1993]. Mercury is exceptional and exists primarily as Hg 0 vapor in the near‐source plume [e.g., Bagnato et al , 2007; Martin et al , 2011a] although recent model studies [ von Glasow , 2010] have suggested that particulate Hg II forms downwind due to reactive halogen chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case for atmospheric mercury (Hg) which is a key contaminant in biochemical processes as well as in air, water and soils, for which volcanism may be an important natural contributor (Varekamp & Buseck 1986;Nriagu & Becker 2003;Pyle & Mather 2003;Bagnato et al 2007Bagnato et al , 2011Martin et al 2012). In volcanic plume gaseous elemental mercury (Hg 0 or GEM) is the dominant species (≥90%; Slemr et al 1985;Schroeder & Munthe 1998;Bagnato et al 2007;von Glasgow 2010;Martin et al 2011) with an atmospheric lifetime of c. 0.5-1 a (Lindqvist and Rodhe 1985;Slemr et al 1985;Lindberg et al 2007;Aryia et al 2008), allowing it to be transported to great distances from the source. The relative proportions of gaseous Hg 0 (g) and Hg(II) species in volcanic gas plumes, and the ratio of gaseous to particulate Hg forms, have rarely been determined in a systematic way Witt et al 2008a, b).…”
mentioning
confidence: 99%
“…GEM plus RGM) or GEM; see Gustin et al (1999) as an example. For the sake of simplicity, GEM and Hg are used without distinction in this article unless otherwise specified since in volcanic emissions GEM is the dominant form (≥90%; Bagnato et al 2007;Zambardi et al 2009;von Glasgow 2010;Martin et al 2011).…”
mentioning
confidence: 99%